The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.3329/jard.v4i1.762
|View full text |Cite
|
Sign up to set email alerts
|

Fish Parasitological Studies in Bangladesh: A Review

Abstract: Fish parasitological investigation and research performed in Bangladesh has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 6 publications
0
22
1
Order By: Relevance
“…Previous findings have shown that helminthes are mostly found in fresh water fishes where factors such as parasite species and its biology, host and its feeding habitats, physical factors, hygiene of the water body and presence of intermediate hosts contribute to their prevalence and intensity (Chandra, 2006;Hussen et al, 2012). In this study, more males were infected than females (p≤0,05).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have shown that helminthes are mostly found in fresh water fishes where factors such as parasite species and its biology, host and its feeding habitats, physical factors, hygiene of the water body and presence of intermediate hosts contribute to their prevalence and intensity (Chandra, 2006;Hussen et al, 2012). In this study, more males were infected than females (p≤0,05).…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, attention has shifted to fish parasites due to increased aquacultural practices. Information is available on parasites of cultured and wild fish (Chandra, 2006 Disease is an important factor militating against fish production. Many diseases are closely linked to environmental deterioration and stress, once the environment is disturbed, the organisms under such culture systems are stressed (SEAFDEC, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries and aquatic resources are economically, ecologically, culturally and aesthetically important to the nation. In Bangladesh, at present there are 260 freshwater fish species, 12 species of exotic fish, 475 species of marine fish and 60 species of prawn and shrimp available (Chandra, 2006). Fisheries sector contributes to GDP 5.2%, animal protein supply 63% and foreign exchange earning 4.8% for the nation (Chandra, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, at present there are 260 freshwater fish species, 12 species of exotic fish, 475 species of marine fish and 60 species of prawn and shrimp available (Chandra, 2006). Fisheries sector contributes to GDP 5.2%, animal protein supply 63% and foreign exchange earning 4.8% for the nation (Chandra, 2006). Huge amount of fish catches from fresh and marine water during winter season when the natural depression attain shallow water and even dry up, naturally the fish catch attains peak.…”
Section: Introductionmentioning
confidence: 99%